2013
DOI: 10.1155/2013/642632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Addition of Melatonin on the Liquid Storage (5°C) of Mithun (Bos frontalis) Semen

Abstract: The present study was undertaken to assess the effect of melatonin (MT) on sperm motility, viability, total sperm abnormality, acrosomal and plasma membrane integrity, DNA abnormality, antioxidant profiles such as superoxide dismutase (SOD), catalase (CAT), glutathione (GSH) and total antioxidant capacity (TAC), enzymatic profiles such as aspartate amino transaminase (AST), alanine amino transaminase (ALT), and biochemical profiles such as malonaldehyde (MDA) production and cholesterol efflux. Total numbers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
28
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 58 publications
9
28
0
2
Order By: Relevance
“…The HOST results in the present study are in conformation with the studies of Ashrafi et al (), El‐Raey, Badr, Assi, & Rawash () in bulls; Perumal et al (), Perumal et al () in Mithun; Chankitisakul () in boars at 15˚C and Izadpanah et al () in stallions; in which plasma membrane integrity improved with the addition of melatonin.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The HOST results in the present study are in conformation with the studies of Ashrafi et al (), El‐Raey, Badr, Assi, & Rawash () in bulls; Perumal et al (), Perumal et al () in Mithun; Chankitisakul () in boars at 15˚C and Izadpanah et al () in stallions; in which plasma membrane integrity improved with the addition of melatonin.…”
Section: Discussionsupporting
confidence: 92%
“…The results of acrosomal integrity in melatonin treated semen are similar to those reported by Cheuqueman et al (), Kapadiya et al (), Pang et al () in bulls; Perumal et al (), Perumal et al () in Mithun; El‐Raey, Badr, Rawash, and Darwish () in goats and Martin‐Hidalgo et al () in boars. The present study is in conclusion of melatonin capacity in shielding acrosomal characters by keeping check on hazardous effects encountered during cryopreservation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It was also reported that melatonin minimizes or prevents the in vitro sperm capacitation and inhibit apoptotic like changes which indicates it has a direct action on spermatozoa. Inclusion of melatonin into the ram sperm (Ashrafi et al, 2011), boar sperm (Hyun-Yong et al, 2006), bull sperm (Ashrafi et al, 2013) and mithun (Perumal et al, 2013d) has been reported that it protected the sperm against the harmful effects of free radicals or ROS and improved the sperm motility, membrane integrity and ferility in the frozen state.…”
Section: Introductionmentioning
confidence: 99%
“…Using semen cryopreserved in extender containing hen's egg yolk (EY), Mondal, Karunakaran, Lee, and Rajkhowa () inseminated 16 mithun cows and achieved 12 pregnancies. When reduced glutathione as an antioxidant was added in the extender, improvement in quality of mithun semen was observed (Perumal, Vupru, & Rajkhowa, ). Although researchers have used diluters of varied composition to limit the cellular damages, the EY remains a most common component.…”
Section: Introductionmentioning
confidence: 99%